2017
DOI: 10.1016/j.tre.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A new look at the morning commute with household shared-ride: How does school location play a role?

Abstract: Recent studies examined the households' trip-timing decisions where adults have to drive their children to school. These studies focus on the cases where school is near workplace. However, different school locations can affect travels and activity patterns significantly. This study re-looks at the household shared-ride problem where school is near home. It is found that the resulting dynamic commuting equilibrium has very different properties, which have been examined and discussed accordingly. Three managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This highlights the importance to appropriately explore the pricing strategies of the parking sharing platform operator. In summary, this study improves and enhances our understanding of the parking sharing, pricing, and management, and also enriches the literature on the two-sided markets, where ride sharing/sourcing has attracted much more attention (Agatz et al, 2012;Wang et al, 2016;Zha et al, 2016;Chen et al, 2017;Zhang et al, 2017;Wang et al, 2018;Bai et al, 2019).…”
Section: Introductionsupporting
confidence: 53%
“…This highlights the importance to appropriately explore the pricing strategies of the parking sharing platform operator. In summary, this study improves and enhances our understanding of the parking sharing, pricing, and management, and also enriches the literature on the two-sided markets, where ride sharing/sourcing has attracted much more attention (Agatz et al, 2012;Wang et al, 2016;Zha et al, 2016;Chen et al, 2017;Zhang et al, 2017;Wang et al, 2018;Bai et al, 2019).…”
Section: Introductionsupporting
confidence: 53%
“…Latterly, Qian et al [14,15] considered various impact factors including parking capacity allocations, parking fees and access times for traffic congestion mitigation, and total social costs reduction. In addition, extensions of bottlenecks could also be found like day-to-day travel behavior evolution [16], preference of autonomous vehicle users [17], and travel choice of shared-riders [18,19]. Highly correlated with the work in this paper, Fosgerau and Small [20] investigated the bottleneck model with variable capacity in the rush hour in the hypercongestion environment.…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, Zhang et al (2017) revisited the household travels with a different school location choice. In these papers, it is found that the appropriate schedule coordination between school and work start time can significantly reduce the total travel cost.…”
Section: Other Studies In Bottleneckmentioning
confidence: 99%
“…However, the work schedule choices were scarcely discussed in these household studies. Only in Zhang et al (2017) the differentiated school and work schedules were examined preliminarily without the consideration of productivity effect. Therefore, this thesis fills the research gap to examine how the commuters with multiple trip purposes behave in their work schedule choices.…”
Section: Other Studies In Bottleneckmentioning
confidence: 99%
See 1 more Smart Citation